À l’épreuve de la « Bastille de Barberousse ». Trajectoire carcérale d’Arezki Kehal et des militants du PPA sous le Front Populaire - Nadia Biskri Berkane (Criminocorpus)
Arezki Kehal’s penal trajectory and prison experience in Algeria's civil prison, known as Barberousse, provides a glimpse of the judicial and prison response orchestrated in Algeria under the Front Populaire by the colonial authorities to combat the radical nationalism of the Algerian People's Party (Parti du Peuple Algérien, PPA). The detention of Arezki Kehal also reveals how prison, instituted in Algeria by the colonial state at the very beginning of the French conquest, was used in the inter-war period for political and militant purposes by the new independence party created by Messali Hadj in March 1937, after the dissolution of the Etoile Nord-Africaine. The “Bastille de Barberousse” played a central role in the politicization of prisoners, in the face of the repressive colonial machinery designed to counter the independence aspirations of Algerian nationalists. For Arezki Kehal and his fellow PPA prisoners, the prison became a front for political struggle, foreshadowing the strategies implemented by FLN (Front de Libération Nationale) and MNA (Mouvement National Algérien) frontline prisoners during the Algerian War of Independence.